2013
DOI: 10.2217/imt.13.24
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor Agonists: Current Status and Future Perspective on their Utility as Adjuvants in Improving Antic Ancer Vaccination Strategies

Abstract: Toll-like receptor (TLR) agonists possess remarkable properties, particularly with regard to dendritic cell activation, promoting Th1-type cytokine production and optimizing cytotoxic T-cell responses. Preclinical and clinical studies conducted to date show that TLR agonists can improve currently applied anticancer vaccination protocols. Although these have resulted in the US FDA approval of three TLR agonists for use in humans, their abundant application encounters limitations, principally due to dose-limitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 99 publications
0
34
0
6
Order By: Relevance
“…Although TLR agonists have often been used in experimental and clinical studies as an immune adjuvant [27], many are associated with significant side effects or toxicity [37,38]. FimH represents a recently discovered TLR4 ligand with a great potential to be a safe and effective immune modulator, particularly amenable for mucosal application based on its selective effect on APCs [39].…”
Section: Discussionmentioning
confidence: 99%
“…Although TLR agonists have often been used in experimental and clinical studies as an immune adjuvant [27], many are associated with significant side effects or toxicity [37,38]. FimH represents a recently discovered TLR4 ligand with a great potential to be a safe and effective immune modulator, particularly amenable for mucosal application based on its selective effect on APCs [39].…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] Stimulation of TLR on DC can also facilitate the induction of Th1 immune responses. 39,40 In a review of several vaccine studies for malignant melanoma, Engel-Noerregaard reported significantly higher response rates in patients who received adjuvants as a part of their vaccine regimen. 41 Poly-ICLC (Hiltonol) is an inosine and cytidine-rich double stranded RNA that stimulates TLR3 and activates DC through a TLR-domain containing adapter inducing interferon-b (TRIF).…”
Section: Adjuvant For DC Vaccinesmentioning
confidence: 99%
“…In three of these cases, adjuvant activity was definitively shown to activate the TLR pathway in DC. 47,49,51 More study is needed, however, because the role of TLR in DC activation has been extensively and recently reviewed 40,54 and one theme that has emerged is that TLR activation in murine models cannot be easily extrapolated to human models because murine and human DC constitutively express a different overlapping set of TLR. DC, exposed to antigen can be matured in vitro or in vivo.…”
Section: Adjuvant For DC Vaccinesmentioning
confidence: 99%
“…Therefore, the use of TLR agonists to mature DCs either ex vivo or in situ is an attractive method for initiating or promoting antitumor responses (Baxevanis et al, 2013). Lung cancer is the most common cause of death from cancer, as it is responsible for approximately 13.5% of all cancer deaths (Ferlay et al, 2007;Prado-Garcia et al, 2012), and the 5-year survival rate in lung cancer is less than 15% (Jemal et al, 2009).…”
Section: Introductionmentioning
confidence: 99%